Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

(Cot a+cosec a-1)/(cot a-cosec a+1)=(1+cos a)/sin a

Cot Acosec A1cot Acosec A11cos Asin A class=

Sagot :

Answer:

Step-by-step explanation:

[tex]\frac{cota+coseca-1}{cota-coseca+1} \\=\frac{cota+coseca-(cosec^2a-cot^2a)}{cota-coseca+1} \\=\frac{(cota+coseca)-(coseca+cota)(coseca-cota)}{cota-coseca+1} \\=\frac{(cota+coseca)[1-coseca+cota]}{(cota-coseca+1)} \\=cota+coseca\\=\frac{cosa}{sina} +\frac{1}{sina} \\=\frac{cosa+1}{sina}[/tex]